Seismic performance evaluation of two-storey moment-resisting pre-cast concrete industrial structures - Kulaksizoğlu, Ahmet Ata. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
Turkey, as a country with majority of its soil prone to high seismic risk, did not only suffer from earthquakes in terms of life casualties, but it also suffered economically. Many industrial structures have been subjected to severe damage, especially in 1999 Marmara Earthquake. Considering an important amount of industrial structures in Turkey are made using pre-cast concrete technology, it is crucial to investigate seismic performance of precast concrete industrial structures. The buildings that are analyzed in this study possess several important aspects specific to themselves, including very large spans and loading, staged construction and differing connection conditions of columns at storey level and the roof. In this study, two pre-cast buildings, with differing storey heights, are analyzed and designed in accordance with Turkish Seismic Code 2007 (TSC 2007). Seismic performance analyses of these two buildings are done using linear and nonlinear methods of TSC 2007. In light of the results obtained, design strategies are developed in order to improve seismic performance of this type of pre-cast industrial structures. The first strategy is to design the two frames using cracked section rigidities and the second strategy is to strengthen one-storey columns that cease at first floor. Totally six frames, including the ones that are designed using developed performance improving strategies, are investigated analytically to determine their seismic performance. Although it should be kept in mind that further and more detailed research is needed to support this study, the results obtained are interpreted to draw the following conclusions and recommendations: • This type of pre-cast structures designed using uncracked section rigidities do not satisfy target seismic performance level (Life Safety Level) specified in TSC 2007. However, same structures designed using cracked section rigidities satisfy target seismic performance level. • Strengthening one-storey columns prevents plastic behaviour to accumulate in their sections and improves overall seismic performance of the structure. • Nonlinear static analysis methods do not yield reliable results for this type of structures and should be supported by nonlinear dynamic analysis methods. • Since design of beams is governed by very large gravitational loading and the connections of pre-cast frames are designed considering amplified seismic loads, beams perform well in this type of pre-cast structures. The seismic performance of these buildings is governed by behaviour of columns..
Keywords: Earthquake resistant design.; Buildings -- Earthquake effects.; Precast concrete construction.